2003
DOI: 10.1007/bf03030296
|View full text |Cite
|
Sign up to set email alerts
|

Differences in photosynthetic characterization of salt tolerance for two rice (Oryza sativa) cultivars

Abstract: We photosynthetically characterized two rice cultivars -salt-sensitive ~Annapurna', and salt-tolerant 'Don~in' -growing under NaCI stress. Both cultivars showed an increase in Fo/Fm (the ratio of initial to maximal chlorophyll fluorescence) and a decrease in Fv/Fm (an indicator of the photochemical efficiency of PS II). In particular, the Fv value for Annapurna significant declined while FJFm was enhanced when plants were exposed to salt stress for 4 d. Annapurna also exhibited more rapid decreases in the coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Cultivars differing in stress tolerance exhibit contrasting expression profiles, as demonstrated for salt and drought stress, where increasing sensitivity is positively correlated with an increasing number of differentially expressed stress-related genes ( Walia et al 2005 ; Degenkolbe et al 2009 ). Among japonica cultivars, Dongjin is considered to be more salt tolerant than Nipponbare ( Oh et al 2003 ; Ferdose et al 2009 ) and we observed a greater reduction of root FW and DW of empty-vector control plants in the Nipponbare background as compared with Dongjin wild-type plants under salt stress (Fig. 4 C), fitting the observed expression of stress marker genes.…”
Section: Discussionsupporting
confidence: 77%
“…Cultivars differing in stress tolerance exhibit contrasting expression profiles, as demonstrated for salt and drought stress, where increasing sensitivity is positively correlated with an increasing number of differentially expressed stress-related genes ( Walia et al 2005 ; Degenkolbe et al 2009 ). Among japonica cultivars, Dongjin is considered to be more salt tolerant than Nipponbare ( Oh et al 2003 ; Ferdose et al 2009 ) and we observed a greater reduction of root FW and DW of empty-vector control plants in the Nipponbare background as compared with Dongjin wild-type plants under salt stress (Fig. 4 C), fitting the observed expression of stress marker genes.…”
Section: Discussionsupporting
confidence: 77%
“…The exogenous application of GB and Cho in the culture media would provide an alternative way for improving the defense mechanisms of plants to salt stress [64]. Rice has been reported as being a GB non-accumulator, while GB has been detected in small amounts in rice cultivars exposed to salt stress, including KDML105 [65], Homjan [66], and Annapurna and Dongjin [67]…”
Section: Exogeneous Application Of Gb In Plants Enhancing Abiotic Stressmentioning
confidence: 99%
“…As chaperones for specific membrane proteins, lumenal immunophilins have been linked to thylakoid membrane assembly during chloroplast biogenesis in cereals (Blomqvist et al 2008, Gollan and Bhave 2010a), and may also be important for acclimation mechanisms involving reorganization of membrane complexes, such as state transitions and cyclic electron flow (CEF), which maintain balanced ATP and NADPH production under fluctuating environmental conditions (Allen 2002). State transitions and CEF are also coping mechanisms for plants in stress conditions and are implicated in temperature and salt tolerance in cereals and other crops (Clarke and Johnson 2001, Lu et al 2008, Oh et al 2003, Wise et al 2004), presenting the immunophilins in the cereal thylakoid as clear candidates to study the fine‐tuning of cereal photosynthesis in response to environmental conditions. This work investigated three thylakoid‐localized FKBPs in wheat, and is the first functional characterization of lumenal immunophilins from a cereal plant.…”
Section: Introductionmentioning
confidence: 99%